Bioinformatics analysis and identification of upregulated tumor suppressor genes associated with suppressing colon cancer progression by curcumin treatment - Wu, Dan; Fu, Zhenkai; Liu, Wenna; Zhao, Yujia; Li, Wenxuan; Liu, Qingqing; Liang, Ying (Frontiers in Pharmacology, 2023)
Tumor suppressor genes (TSGs) are commonly downregulated in colon cancer and play a negative role in tumorigenesis and cancer progression by affecting genomic integrity, the cell cycle, and cell proliferation. Curcumin (CUR), a Chinese herb-derived phytochemical, exerts antitumor effects on colon cancer. However, it remains unclear whether CUR exerts its antitumor effects by reactivating TSGs in colon cancer. Here, we demonstrated that CUR inhibited HT29 and HCT116 proliferation and migration by cell-counting kit-8, colony-formation, and wound-healing assays. Furthermore, the comprehensive bioinformatics analysis of mRNA sequencing revealed that 3505 genes were significantly upregulated in response to CUR in HCT116 cells. Kyoto Encyclopedia of Genes and Genomes and Gene Ontology analyses showed that the most upregulated genes were enriched in cancer pathways containing 37 TSGs. Five (ARHGEF12, APAF1, VHL, CEBPA, and CASP8) of the 37 upregulated TSGs were randomly selected for real-time fluorescence polymerase chain reaction and the verification results showed that these five genes were significantly reactivated after CUR treatment, suggesting that TSGs are related to CUR-mediated colon cancer inhibition. ARHGEF12 is a newly identified TSG and a potential therapeutic target for colon cancer. Furthermore, molecular docking was performed to predict the binding sites of CUR and ARHGEF12, suggesting that CUR can prevent colon cancer cell invasion and metastasis by inhibiting ARHGEF12 and RhoA binding. In conclusion, the present study reveals that CUR inhibits colon cancer cell proliferation and migration by reactivating TSGs, revealing a new mechanism and potential target for colon cancer treatment.